Prosedur Perceraian Ditinjau Berdasarkan Hukum Fiqh dan Hukum Positif - Lilis Handayani (Journal of Legal and Cultural Analytics, 2022)
This article describes the divorce procedure in terms of fiqh law and positive law. The purpose of writing this article is as education, information and advocacy to readers so that divorce is carried out in a civilized manner by prioritizing fiqh legal procedures and positive law. This type of research is qualitative legal research and normative legal research, namely what we know as library law research, namely legal articles that are carried out by researching based on materials sourced from libraries. Sources of data used by the author in this article include primary legal materials, namely applicable laws and regulations that provide descriptions of primary legal materials in the form of interpretations, general books, journals, documents and other references related to this article. From the results of writing this article are: First, the husband has the authority to give talaq or divorce his wife if the problem at hand does not have a solution to the problem. Second, divorce should follow the legal mechanism of fiqh and positive law based on applicable regulations. Third, husband and wife should always prioritize peaceful mediation and avoid conflicts that can trigger household damage.